Impacts of fragmentation and neighbor influences on farmland conversion: A case study of the Edmonton-Calgary Corridor, Canada. (November 2015) - Qiu, Feng; Laliberté, Larry; Swallow, Brent; Jeffrey, Scott
Highlights: Quantify land fragmentation within the context of agriculture. Examine effects of fragmentation and neighboring influences on farmland conversion. Increases in fragmentation further encourage farmland conversion. Land-use activities and decisions have strong spillover effects on neighboring areas. To design and implement effective strategies, regional policy makers need to collaborate and cooperate with each other. Abstract: Under heavy development pressure, farmland is rapidly being converted to non-agricultural uses such as houses, roads, and industrial uses. A great deal of research has investigated these farmland losses and their associated drivers. However, the existing empirical studies have neglected two important issues related to farmland conversion: spillover effects from neighboring areas and the impacts of farmland fragmentation. This study incorporates fragmentation and neighboring impacts into the farmland conversion analysis and provides new insights for the land-use/cover change literature. Empirical results indicate that increases in fragmentation further encourage farmland conversion to urban uses, but the effects are not linear with decreasing marginal influences. Land-use activities and decisions have strong spillover effects on neighboring areas. Ignoring this externality could result in biased estimates and marginal effects and thus misleading policy decisions and recommendations.